The use of prepositions among adult ESL learners in Malaysia - Sudhakaran, Beena (2010)
One predicament facing an educationist is whether grammar should be taught formally, or allowed to be naturally acquired, especially where there has generally been a deterioration of students’ grammar skills among English as second language (ESL) learners in Malaysia, particularly in the use of a syntactical category like prepositions.